Evaluation of the Implementation of Inclusive Education in Junior High Schools - Putri, Muggia Usmi Eka; Ghani, Abd. Rahman A; Al Jufri, Hamid (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The objective of this study is to evaluate, measure, and prove the gaps in various components—design, installation, process, and product—so that it can provide information for improvement and development related to National Education Standards in building Inclusive Education in Junior High Schools in Tangerang. The evaluation model approach used in this study is the Discrepancy Evaluation Model, or Gap Evaluation Model, developed by Malcolm M. Provus. This research method is a mixed method, not only qualitative descriptive evaluation and quantitative, but also a combination of both. The evaluation subjects were 15 people, including the principal; the vice principal for curriculum, public relations, student affairs, and facilities and infrastructure; teachers; parents; and students. The results indicate that the design aspect, with a discrepancy of 28% in the management standard indicator, falls within the